Digestibility of ingredients in two pelleted diets by macrobrachium rosenbergii (de man) - Sian, Kenneth Chin Sui (Fakulti Pengajian Maritim dan Sains Marin, 2011)
The digestion coefficients of nutrients in two diets containing 307, and 407. protein were evaluated in the Malaysian giant freshwater prawn Macrobrachlum rosenbergii. Chromic oxide was used as an internal marker for the evaluation of digestibility. Evaluations were carried out with juvenile and adult prawns including female prawns undergoing three different stages of gonad maturation. The results indicate, that the adult prawns were able to digest the nutrients of the ingredients better than'" the juveniles. In the two diets te's't'ed* co pr a c ake , ^whea t flour and soyabean meal we^e better digested than^rish meal and shrimp meal for both juvenile and -adult—prawns. Copra cake was found to be a good source of lipids (71-1007.) , carbohydrate (85-967.) and dry matter ( 72-927.) as well as a good attractant. Carbohydrate, gross energy and dry matter were very well digested in wheat flour with values of 931007., 86-957, and 85-977, respectively. Soyabean meal gave good digestion coefficients for protein (84-997.), lipid (90977.) and carbohydrate (80-1007,). The results indicated that copra cake, wheat flour and soyabean meal are good sources of nutrients for M. rosenbergii. No differences in digestibility was observed for the female prawns with green, yellow and orange gonads. This showed that the stage of gonad maturation has no significant effect on digestibility.